An estimation of amount greenhouse gas emissions in agricultural waste treatment systems in the Odessa oblast - Біньковська, Г. В.; Шаніна, Т. П. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2016)
Greenhouse gases retain radiation in the Earth’s atmosphere and contribute to its excessive heating. Human activity, related to agriculture and burning of fossil fuels, is the main source of greenhouse gas emissions influencing the climate change. The greenhouse gas emissions due to the agricultural activities have almost doubled for the last 50 years. They tend to further increase by 30 percent up to 2050, if no measures are taken to reduce their content. The paper aims at assessment of the volume of greenhouse gas emissions, generated in various systems of agricultural waste treatment by the districts of the Odessa oblast, and development of recommendations for selection of measures to reduce the greenhouse gas emissions. Analysis of the calculated data reveals significant excess of the volumes of greenhouse gas emissions in traditional agricultural waste treatment systems over the emissions in the course of anaerobic fermentation of biomass.